Organizational context and knowledge transfer: the mediating effect of organizational socialization in Malaysian service organizations - Islam, Md. Zahidul (2007)
The purposes of this study were to (a) examine the extent of knowledge transfers in Malaysian service industry, and (b) investigate the relationship between organizational context, information and communication technology, organizational socialization and knowledge transfer.